PERANAN PENYULUHAN DAN PELATIHAN UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM LAYANAN WISATA TELUK KILUAN LAMPUNG - Aryanti, Nina Yudha; Windah, Andi; Atika, Dewie Brima (Indonesian Journal of Socio Economics, 2019)
Teluk Kiluan has the potential for marine tourism that can be relied upon to increase local revenue. The existence of rare bottle dolphins is a special attraction. This condition is supported by a multi-ethnic local culture and local community participation by providing homestay services. The purpose of this study was to determine the role of counseling and training to increase community participation in Teluk Kiluan tourism services in Lampung. This research uses a qualitative descriptive method; the respondents in this study were 34 homestay managers. The results of the study indicate that the sharing of training activities carried out is fully supported through the active participation of the target community. The training activities carried out included tourism management training, village website creation and the creation of promotional media, as well as, english. some obstacles in increasing community active participation in tourism services are the low level of education and the economy of the community; the community is concentrated in the agriculture and fisheries sector so that the service sector has not been made a leading sector in improving the economy. This condition is also supported by the lack of facilities and infrastructure that support tourism services.Â  Â Keywords: extension, marine tourism, society participation